PORTFOLIO ASSESMENT AS A CATALYST OF PROCESS-ORIENTED SKILL TO PROMOTE STUDENTS IN WRITING BUSINESS LETTERS - Yulian, Ryani; Yuniarti, Yuniarti (Journal of English Education Program, 2020)
The purpose of this study was to improve the writing skill of the Management students at Faculty of Economics and Business Universitas Muhammadiyah Pontianak. A classroom action research was employed to conduct a portfolio assessment as a process-oriented skill. Students are expected to be able to write various kinds of business letters to fulfill the needs of their future career. The ability of how to write well cannot be obtained through a product-oriented approach particularly to students with low level English skill. Therefore, this study aimed at improving students’ writing skill in terms of writing business letters namely letter of offer. The samples consisted of 37 students of Business English subject in the academic year 2018/2019. The findings of the study proved significant improvement on students’ writing with portfolio assessment in terms of sub-skills in writing namely text harmony, vocabulary selection, grammar option, vocabulary writing, and writing tidiness from the first cycle to the second cycle. Subsequently, the students can orderly produce piece of writing since the underlying purpose of this study was to encourage writing as process-oriented skill.